Genome and single-cell RNA-sequencing of the earthworm Eisenia andrei identifies cellular mechanisms underlying regeneration - Yong Shao (Nature Portfolio, 2020)
The mechanisms regulating regeneration of the earthworm are unclear. Here, the authors use genomic and transcriptomic analysis of the earthworm Eisenia andrei together with Hi-C analysis to identify genes involved and show activation of LINE2 transposable elements on regeneration.